Impact of Event Marketing, Promotions, and Brand Image on User Loyalty: A Study on Bukalapak Marketplace - Ma’arif, Syamsul; Putri, Anita Afifa (Jurnal Ekonomi dan Bisnis Digital, 2025)
Competition in Indonesia’s e-commerce sector is increasing, leading Bukalapak to revise its operational strategies due to declining competitiveness. This study investigates the effects of event marketing, promotions, and brand image on user loyalty. Using a quantitative method, data were collected via questionnaires from 180 respondents and analyzed through multiple linear regression in SPSS. Event marketing had a negative effect (t = -2.127, p = 0.035), promotions had a significant positive effect (t = 6.347, p = 0.000), while brand image showed no significant influence (t = 0.376, p = 0.707). The F-test indicated a joint significant effect (p = 0.000). The coefficient of determination (R²) was 20.1%, implying that other variables also influence user loyalty.